An Efficient Framework for Sharing a File in a Secure Manner Using Asymmetric Key Distribution Management in Cloud Environment. (27th June 2019) - Pradeep, K. V.; Vijayakumar, V.; Subramaniyaswamy, V.
Abstract : Cloud computing is a platform to share the data and resources used among various organizations, but the survey shows that there is always a security threat. Security is an important aspect of cloud computing. Hence, the responsibility underlines to the cloud service providers for providing security as the quality of service. However, cloud computing has many challenges in security that have not yet been addressed well. The data accessed or shared through any devices from the cloud environment are not safe because they are likely to have various attacks like Identity Access Management (IAM), hijacking an account or a service either by internal/external intruders. The cryptography places a major role to secure the data within the cloud environment. Therefore, there is a need for standard encryption/decryption mechanism to protect the data stored in the cloud, in which key is the mandatory element. Every cloud provider has its own security mechanisms to protect the key. The client cannot trust the service provider completely in spite of the fact that, at any instant, the provider has full access to both data and key. In this paper, we have proposed a new system which can prevent the exposure of the key as well as a framework for sharing a file that will ensure security (CIA) using asymmetric key and distributing it within the cloud environment using a trusted third party. We have compared RSA with ElGamal and Paillier in our proposed framework and found RSA gives a better result.